First occurrence of rudderfish Centrolophus niger (Gmelin, 1789) in the Edremit Bay (Northern Aegean Sea, Türkiye) with the maximum length record for Turkish Seas - Cengiz, Özgür; Şenol Paruğ, Şükrü; Berkay Aydemir, Kadir (African Journals Online (AJOL), 2023)
Climate change is one of the crucial factors affecting the geographical distribution of fish species. However, the maximum size is an indication of whether there is overfishing pressure on a fish species or the current ecological conditions in which it is located. A single specimen of recently died (rigor mortis has not yet formed) Centrolophus niger was incidentally found inshore on January 27, 2023, off the Burhaniye coast (Edremit Bay, Northern Aegean Sea, Türkiye). The present study indicates both the first observation of C. niger for Edremit Bay and its maximum length for Turkish seas.
Keywords: Centrolophus niger; Maximum size; Occurrence; Edremit Bay; Türkiye.; 14. Life underwater